Analisis Pelaksanaan Kebijakan Kota Layak Anak (Studi Kasus Pelaksanaan Program Ruang Bermain Ramah Anak di Ruang Terbuka Hijau Kacang Mayang Kota Pekanbaru) - Pivit Septiary Chandra; Sonia Sischa Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study aims to see the implementation of child-friendly city policies in the Kacang Mayang Green Open Space, Pekanbaru City. This type of research is qualitative with descriptive analysis. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior from the phenomena that occur. This study examines the facts of the implementation of the Child Friendly Playroom Program in Pekanbaru City. The data collection technique in this research uses literature study by collecting data and documents from various references that will be used as references. The results of this study are that the implementation of child-friendly city policies (a case study of the implementation of the Child Friendly Playroom Program in the Kacang Mayang Green Open Space in Pekanbaru City) has gone well. This is shown by the availability of adequate facilities, infrastructure and facilities to become child-friendly green open spaces. Received a good assessment and determined that Pekanbaru's Kacang Mayang Green Open Space was suitable for children, proving the government's commitment to realizing a child-friendly city through the provision of child-friendly green open spaces. In implementing child-friendly city policies, there are several factors that influence, namely: completeness of the facilities; Accessibility; Safety and comfort; Government commitment.